A Patient with Vesicoureteral Reflux Due to Neurogenic Bladder with Complications of Chronic Kidney Disease - Eka Dharma Putra, I Putu (International Journal of Psychology and Health Science, 2025)
Vesicoureteral reflux (VUR) is the backward flow of urine from the bladder into the upper urinary tract and is more commonly observed in children compared to adults. Adult-onset VUR is relatively rare and often linked to secondary causes such as neurogenic bladder or post-surgical complications. This case report presents a 56-year-old male patient with secondary VUR due to neurogenic bladder, complicated by chronic kidney disease (CKD) stage V. The patient exhibited symptoms including increased urinary frequency, difficulty controlling urination, and pubic pain. Diagnostic findings included severe hydronephrosis, detrusor overactivity with small bladder capacity, and lumbar spondylosis with nerve root compression. Management involved medical therapy with antimuscarinic agents and preoperative hemodialysis to optimize renal function. Surgical intervention was recommended, but the patient opted for continued regular hemodialysis. This case underscores the importance of early diagnosis and integrated. management of VUR and its complications to prevent CKD progression. Case report: A 56-year-old male presented with chronic urinary frequency and discomfort, significantly disrupting daily activities. Medical history revealed recurrent episodes over three years, worsening recently. Imaging and diagnostic evaluations showed severe hydronephrosis and evidence of neurogenic bladder due to lumbar nerve compression. Laboratory tests indicated CKD stage V, with anemia, elevated creatinine, and proteinuria. Treatment included solifenacin and preoperative hemodialysis, but the patient declined surgery. Regular dialysis was initiated as the primary management. Discussion: The etiology of adult-onset VUR is often secondary to structural or neurological abnormalities. In this case, lumbar spondylosis led to neurogenic detrusor overactivity, causing reflux and subsequent renal damage. Pathophysiology involves bladder dysfunction and intrarenal reflux, which aggravates kidney scarring. Integrated care, combining medical and potential surgical management, remains critical in mitigating disease progression. Conclusion: This case highlights the complexity of secondary VUR in adults, emphasizing the need for a multidisciplinary approach to management. Early identification and tailored treatment are pivotal in preventing severe complications like CKD.